Analysis of recruitment process by digital media and social networking in international companies in latin america and the effects on their financial performance - Lasso Silva, Esteban Antonio (2018)
Recruitment processes play a particularly important role on Human Resource Management and on the overall business planning. Its main objective is to find and attract suitable and potential talent based on the company’s needs and requirements. With the use of informatics tools and electronic resources, recruitment processes have evolved into faster, simpler, more accessible, and more efficient mechanisms for candidates’ search. Consequently, recruiters have developed several alternatives of online procedures, having webpages, job boards, and social networks as the main channels. With all this, companies are able to develop strategic and competitive Human Resource Management, obtaining advantages such as reaching a wider audience, reducing costs, and even promoting employer branding. Even so, companies are not the sole beneficiaries of the implementation of e-recruitment systems, but individuals as job seekers obtain substantial advantages, making it extremely relevant to understand consumer behavior so as to determine what elements influence it. Concerning the Latin American region, e-recruitment represents an opportunity and great potential for international companies to develop online strategic procedures regarding Human Resource Management. Therefore, the present research is based on four theoretic frameworks that involve all the necessary elements for its development, being these Web 2.0 Theory, E-Recruitment as part of a Human Resource Theory, Economic and Psychoanalytic Consumer Behavior Theories. In this way, it is centered on demonstrating the impact of e-recruitment on international companies and consumers through a descriptive and exploratory methodology, taking into consideration theoretical and empiric elements.